Does Economic Development Impact CO2 Emissions and Energy Efficiency Performance? Fresh Evidences From Europe - Liu, Hongying; Wang, Kuan-Ting; Khudoykulov, Khurshid; Tai, Tran Duc; Ngo, Thanh Quang; Phan, Thi Thu Hien (Frontiers in Energy Research, 2022)
Data from a survey of 21 European nations from 2006 to 2018 investigates the relationship between economic development and carbon dioxide emissions. The PCA of normalised factors is used to create three quantitative measures for financial intermediation dependent on the results of the study. When estimating the framework, we used the Hoechle method, which generates systematic deviation for linear panel styles that really are not homoskedasticity coherent and moreover resistant to broad types of cross-sectional dependency. We observe that earnings, resource utilization, industrialization, urbanisation, foreign direct investment, and the banking system all seem to have contributed to increased carbon dioxide emissions in the area. However, greater economic access appears to have resulted in a reduction in greenhouse gas emissions. In terms of quality, the results are resilient to a variety of alternative proxies for financial inclusions as well as acceptable changes to the conceptual framework. According to the empirical findings, there are currently no regulatory interactions linking increasing economic development and reducing carbon dioxide emissions at the national level. As a result, economic growth should be incorporated into the implementation of sustainable green economy plans at the municipal, provincial, and city levels, particularly to counteract the documented detrimental impact of higher carbon dioxide emissions associated with increased financial inclusion.